Pemanfaatan Media Visual Dalam Program Edukasi Gizi Untuk Mencegah Konsumsi Gula Berlebih Di Kalangan Remaja - Dianthi, Martha Heriniazwi; Handayani, Tita Septi; Maryaningsih, Maryaningsih; Lestari, Septyca Tri; Suryadi, Aprilia; Liza, Monika (Jurnal Dehasen Untuk Negeri, 2025)
BerbaExcessive sugar consumption among adolescents poses a significant public health concern due to its association with obesity, diabetes, and other metabolic disorders. This Community Service Program (PKM) aimed to enhance nutritional literacy and raise awareness among teenagers regarding the dangers of excessive sugar intake through the use of communicative and engaging visual media. The target participants were students of SMA 4 Kota Bengkulu, with face-to-face education, interactive discussions, and distribution of visual media such as booklets and educational videos. The program was a cross-disciplinary collaboration involving the Departments of Communication, Nursing, and Computer Science at Universitas Dehasen Bengkulu. Results indicated improved student understanding of sugar-related health risks, enhanced ability to read nutrition labels, and more critical attitudes in choosing healthier foods. The evaluation suggests integrating nutrition literacy into school curricula and empowering students as change agents. This program offers a positive contribution toward fostering a nutritionally aware and health-conscious younger generation.hasa Inggris